Developing conceptual framework for zakat distribution impact on social welfare using financial technology and its implications on sustainable development goals (SDGs) in OIC countries - Ashurov, Sharofiddin; Syed Jaafar Alhabshi, Syed Musa; Othman, Anwar Hasan Abdullah; Mohammad Habibullah, Habibullah; Mohd Shukri Bin Muhamad Yusof, Shukri (PPZ Kedah, 2019)
Although an Islamic social finance including zakat witness upsurge development in the size which was reached to $2 trillion in 2015 and expected to exceed $3 trillion by 2020, there is lack of transparency and timely reporting which resulted in a mismatch between zakat data collection and distribution. This is due to the lack of adoption the Financial technology spe-cifically block chain and artificial intelligence system in zakat management to facilitate prop-er, timely and effective reporting in all OIC countries. Therefore, this research aims to pro-pose a ‘Islamic Social Welfare Financial Technology’ (ISW FinTech) as an innovative frame-work that assess zakat institutions operational efficiency and effective reporting of zakat col-lection, transparency and efficient distribution. This model will guide zakat management and distribution policies and practices as part of Islamic Social Welfare. It will establish transpar-ent and reliable system that will increase confidence and trust in the society on zakat collec-tion. With a more effective system it will accelerate poverty alleviation initiatives and achieve SDGs among OIC countries.